The future of the Bonny Method: A perspective on Danish practice with a forecast to the future - Lars Ole Bonde (Approaches: An Interdisciplinary Journal of Music Therapy, 2017)
The article presents the current status of the Bonny Method of Guided Imagery and Music (GIM) in Denmark, with an outlook to the international context. The central focus is on the results of a survey (2016) of Danish GIM practitioners (n = 20), with relevant international surveys introduced as comparisons. Clinical applications of the different formats within the ‘spectrum of GIM’ are also presented and discussed in a Danish context; the future potential of the many Bonny Method session formats is then outlined, and implications for training are discussed.